EFL Teachers' Experiences During the Pandemic: Stories From Rural Area in Tungkal Ilir District - Pahrozi Ahmad; Anita Triastuti (IJEE (Indonesian Journal of English Education), 2021)
ABSTRACTThis article explores the implementation of online learning by English teachers in the age of the coronavirus pandemic in the Tungkal Ilir district, West Tanjung Jabung Regency. This article examines two research questions: (1) How do EFL teachers describe their practices and perceptions of online learning during the pandemic, and (2) What challenges EFL teachers face while implementing online learning during the pandemic. In this small-scale qualitative study, three English teachers took part. Semi-structured interviews were used to gather information. The result revealed that teachers in remote areas used social media and digital platforms to carry out their online teaching. On the other hand, these teachers had some issues incorporating online learning. The problems can be divided into two categories: (a) unfamiliarity with the platforms and (b) inability to respond to students quickly. In addition, some suggestions are also given for further researchers to conduct a similar study. ABSTRAKArtikel ini membahas tentang implementasi pembelajaran online oleh guru bahasa Inggris di era pandemi virus corona di kecamatan Tungkal Ilir, Kabupaten Tanjung Jabung Barat. Artikel ini membahas dua pertanyaan penelitian: (1) Bagaimana guru EFL menggambarkan praktik dan persepsi mereka tentang pembelajaran online selama pandemi, dan (2) Apa tantangan yang dihadapi guru EFL saat menerapkan pembelajaran online selama pandemi. Tiga guru Bahasa Inggris diambil sebagai responden dalam studi kualitatif skala kecil ini.  Wawancara semi terstruktur digunakan untuk mengumpulkan informasi. Hasil penelitian menunjukkan bahwa guru di daerah terpencil telah menggunakan media sosial dan platform digital untuk melaksanakan pengajaran online mereka. Disisi lain, guru memiliki beberapa masalah dalam penerapan pembelajaran online. Masalah dapat dibagi menjadi dua kategori: (a) ketidaktahuan dengan platform dan (b) ketidakmampuan untuk merespon siswa dengan cepat. Selain itu, beberapa saran juga diberikan bagi peneliti selanjutnya untuk melakukan penelitian serupa.